Business Innovation of Sports Organization - Kubata, Jan; Kupec, Václav; Kopkáně, Heřman; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
In the turbulent world of sports and business, organizations face constant challenges, bringing the necessity of strategic innovation to light. The bachelor thesis aims to analyze internal resources, perform a comprehensive external environment analysis, and create recommendations and proposals to innovate the organization and enhance their strategy. To achieve this goal, analytical tools such as Stakeholder analysis, PESTEL, Porters Five Forces, Industry Life Cycle, VRIO, Benchmarking, SWOT, and finally Scenario Planning were employed. The findings uncover significant strategic gaps, opportunities, and threats that the organization faces in the constantly changing world such as outdated coaching methods or the limited use of in-game technology. The thesis follows with recommendations to the organization including investing in new in-game technologies or joining international programs to strategically evolve and innovate the organization. If the suggested recommendations for improvement are fully and correctly implemented, the organization can strategically innovate, improve, and grow.
Vedoucí práce: Václav Kupec
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses